Impact in participatory health research: what can we learn from research on participatory evaluation?. Issue 4 (8th August 2017) - Springett, Jane
Abstract: Participatory Health Research is a collective term adopted globally for participatory action research in a health context. As an approach to research, it challenges current ways used within the health sciences to measure research impact as research, learning and action are integrated throughout the research process and dependent on context and participation. The literature on participatory evaluation is explored to see if it can offer some insights into how best to articulate impact. Similar debates are taking place particularly concerning the relationship between degree of participation and impact, how impact should be defined and the role of wider social forces on the evaluation process. A focus on core values, such as social justice, differentiates transformative evaluation from more pragmatic participatory evaluation, but this is poorly conceptualised in evaluation models.